The symbiosis of technology and regulation: how industry 5.0 redefines bank-state interaction for decades to come? - Aleksandrov , Oleksii (Pressing Problems of Public Administration, 2025)
This article explores the symbiosis of Industry 5.0 technologies and regulatory mechanisms that radically transform the interaction between the banking sector and public governance with a perspective extending to 2045. The research identifies key mechanisms of mutual influence between advanced technologies (artificial intelligence, distributed ledgers, quantum computing) and regulatory processes that define the evolution of banks from traditional financial intermediaries into integrated ecosystems of socio-economic development. The theoretical novelty of the study lies in substantiating the concept of «hybrid financial entities», in which technological infrastructure and regulatory processes function as inseparable components of a unified self-adapting system based on principles of proactive compliance and algorithmic trust. The paper demonstrates that the transformation of public governance models in the financial sector is moving from hierarchical structures towards platform solutions («Government as a Platform», GaaP), creating preconditions for regulatory landscape fragmentation and the formation of «regulatory microclimates». The integration of ESG principles into banking regulation redefines the very nature of financial intermediation, transforming banks into institutions of sustainable development. Special attention is paid to ensuring «digital sovereignty» and «safe degradation» of financial systems in conditions of geopolitical instability and risks of global conflicts. The study proposes a methodological table of banking institutions’ characteristics within four scenarios of financial system evolution: «Technological Hegemony», «Regulatory Revenge», «Decentralised Autonomy», and «Hybrid Convergence». The paper argues that the most probable scenario for banking sector evolution by 2045 is «Hybrid Convergence», characterised by a multi-level financial system where centralised and decentralised elements, state regulation and market self-regulation coexist within a unified ecosystem.